INTEGRASI MANAJEMEN JENJANG KARIR PADA LEMBAGA PENDIDIKAN STUDI ANALISIS MEMBANGUN KUALITAS SDM SEKOLAH SWASTA MELALUI PENDEKATAN TEORI SUPER DAN HOLLAND - Akhmad Baizuri (Al Hasanah Barokah Foundation, 2025)
This topic will explore how the integration of Super and Holland's career theories can be applied to improve the quality of human resources (HR) in private schools in Indonesia. In the ever-changing educational context, it is crucial for private schools to focus not only on academic curricula but also on the career development and professionalism of teachers and staff. Private schools in Indonesia often face challenges in maintaining the quality of teaching and human resource management. Among the various approaches available, Super and Holland's theories offer a framework that can help understand and design better career paths for educators. Super's theory emphasizes the importance of lifelong career development, while Holland's theory focuses on the fit between the individual and the work environment. This study analyzes how the application of Super and Holland's theories can help design clear career paths for teachers and staff in private schools. This study also identifies the needs and challenges faced by private schools in implementing this career development model. This study also develops practical recommendations for private schools in integrating this approach into their HR development policies. The results of this study are expected to make a significant contribution to the development of career management models in the education sector, particularly in private schools. By understanding and applying these theories, private schools can better prepare qualified teaching staff, which in turn will improve the quality of education provided to students.